2018
DOI: 10.18697/ajfand.83.17710
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mycotoxin content in soybean (Glycine max L.) grown in Rwanda

Abstract: Soybean is a critical food and nutritional security crop in Rwanda. Promoted by the Rwandan National Agricultural Research System for both adults and as an infant weaning food, soybean is grown by approximately 40% of households. Soybean may be susceptible to the growth of mycotoxin-producing moulds; however, data has been contradictory. Mycotoxin contamination is a food and feed safety issue for grains and other field crops. This study aimed to determine the extent of mycotoxin contamination in soybean, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The data obtained show that soyabean has minimum contamination with all three types of mycotoxins 3 (0.43%), followed by maize and poultry pellets. A screening survey for mycotoxins carried out in Rwanda that soybeans harvested crops were shown a low contamination degree [36]. In contrast, substantial levels of contamination with twenty fungal metabolites toxins mostly belong to Fumonisins were identified in Brazilian maize and poultry feed, which proposed their contribution to exacerbate the risk of mycotoxin toxics exposure in animals and humans [37].…”
Section: Discussionmentioning
confidence: 99%
“…The data obtained show that soyabean has minimum contamination with all three types of mycotoxins 3 (0.43%), followed by maize and poultry pellets. A screening survey for mycotoxins carried out in Rwanda that soybeans harvested crops were shown a low contamination degree [36]. In contrast, substantial levels of contamination with twenty fungal metabolites toxins mostly belong to Fumonisins were identified in Brazilian maize and poultry feed, which proposed their contribution to exacerbate the risk of mycotoxin toxics exposure in animals and humans [37].…”
Section: Discussionmentioning
confidence: 99%
“…Instead, a log-normal distribution (truncated between 0 and the highest observed sample maximum) was assumed and fit to the available data. As the one included study reporting detectable aflatoxin in Nigeria reported a sample maximum of only 2 ng/g, a higher (i.e., more conservative) value of 4 ng/g, reported in a Rwandan study (Niyibituronsa et al, 2019) was used as the upper bound of the truncated distribution. Similarly, as there were scant records of aflatoxin contamination in Nigerian cowpea samples, one record from a neighboring country (Benin) that was identified in the systematic literature review was included in the dataset (Houssou et al, 2009).…”
Section: Soybeanmentioning
confidence: 99%
“…Soybean [Glycine max (L.) Merrill], is among the oldest crop introductions in Rwanda, having been introduced by the Belgians in early 1920's (Niyibituronsa et al, 2018;Shurtleff and Akiko, 2010). However, the crop gained a relatively low interest among farmers until recently, after the government's efforts to boost soybean production.…”
Section: Introductionmentioning
confidence: 99%